Design and implementation car parking allocation system of FPGA and VLSI digital ASIC - Rasidin, Nurul Nabilah (2017)
The number of vehicles on the road increase rapidly for the past 5 years. Due to the increment trend, there are various problems faced due to the limited parking area at public location such as shopping complex, hospital and government building. One of the main problem is the improper allocation management system, this is an issue that must be solved. This proposed system able to help management to install a smart car parking allocation method at a minimum cost. This system able to indicate available and unavailable parking area in a low cost by using a few number of sensors and some buttons at enter and exit gate. This project able to make whole process of car parking allocation more efficient and less complex. In other word, this system ease the user to search an available parking lot and to facilitate the management process. The car parking allocation system is proposed to demonstrate 6 slots display and 20 empty parking lots at each level. The slot are referring to the level and wing that will selected by the user at the parking slot display located at the main entrance. The function of parking slot display are to notify user the availability of parking lot at which level and wing. The available or unavailable of the parking lot at the parking slot display shows by (Light Emitting Diode) LEDs and push button are for user select. The parking lot are divided to two wing which every wing consist of 10 parking lot. The number of parking lot are decided by the system based on the nearest parking lot available to the building entrance, the concept of first come first serve is used. This system implemented using (Field Programmable Gate Array) FPGA board and (Very Large Scale Integration) VLSI digital (Application Specific Integrated Circuit) ASIC flow for presenting the interfacing between software and hardware.